Fitness profiling and comparisons between different standards of competitive junior female tennis players - Stanley, M. (1999)
The purpose of the present study was to profile competitive junior female tennis players and determine if differences in fitness exist between state and district standard players. Tennis relies on the components of skill, psychology and fitness for optimal performance. Fitness allows the player to optimise their playing technique and to greatly reduce the risk of injury. Fitness thus plays an essential role in a player achieving a high level in the sport. A comparison of different fitness components was made between state level (n = 13, age=16.23 yrs) and district level (n = 10, age = 17.10 yrs) female tennis players. The fitness components measured included: maximal aerobic capacity (graded treadmill test to volitional exhaustion with direct oxygen analysis), strength (grip strength), power (vertical jump), speed (20 yard dash), muscular endurance (60second sit-up), agility (spider test), flexibility (sit and reach) and body composition (restricted anthropometric profile). A questionnaire was also administered to determine fitness training habits and attitudes to fitness. A series of unpaired t-tests found no significant differences between the groups on any of the body composition or fitness variables. The only significant difference occurred with the subjects playing age where the state group had been playing tennis for a significantly longer time (8.46 yrs) than the district group (6.55 yrs). The results of the present study showed that the fitness levels of the girls was sub-standard. This may partly explain the current lull in the performance of Australia`s female tennis players. Questionnaire results showed that most girls were spending considerable time doing fitness training each week however, the questionnaire also showed that most of the girls did not have a fitness program to follow and would like a program written for them. To succeed at the highest level the tennis player must be proficient in all three areas of skill, psychology and fitness. The majority (85%) of the girls in the present study were doing some form of fitness training yet their fitness levels were sub-standard. This means that current programs are not providing the junior female tennis players with the necessary fitness requirements, especially with 67% of subjects stating that they would like a program written for them. If the girls are already committing time to fitness they need to be provided with individualised programs that make more efficient use of time, minimise the risk of burnout and injury, and provide maximal fitness gains.